Analisa Penegakan Hukum Terhadap Pembayaran Hak Upah yang Diputus oleh Pengadilan Hubungan Industrial (Studi Kasus Putusan Nomor : 153/Pdt.Sus-PHI/2024/PN Bdg) - Saehudin, Saehudin; Widagdo, Gatot S. (HUMANIORUM, 2025)
The existence of Law Number 6 of 2023 concerning the Stipulation of Government Regulation in Lieu of Law Number 2 of 2022 concerning Job Creation, in Article 88A Paragraph (1) which states that the Rights of Workers/Laborers to Wages arise when an Employment Relationship occurs between the Worker/Laborer and the Employer and ends when the Employment Relationship is terminated, in the Lawsuit for Disputes over Rights to Wages filed with the Industrial Relations Court by workers Adi Priyanto and Yussak Andrian against PT Nippisun Indonesia because the Workers' Wages were not paid even though the Workers' employment relationship had not been terminated and the Panel of Judges who examined the lawsuit issued a Decision in the main case, namely Rejecting the Plaintiffs' lawsuit in its entirety, the legal considerations of which cannot be considered, because they are not legally based. so that it should be declared rejected, then the first problem is how the Payment of Wage Rights in Law Number 6 of 2023 concerning the Stipulation of Government Regulation in Lieu of Law Number 2 of 2022 concerning Job Creation and secondly, how the Legal Considerations of the Industrial Relations Court Panel in decision Number: 153/Pdt.Sus-PHI/2024/PN Bdg, concerning the Case of Payment of Wage Rights have been in accordance with applicable regulations, the research method used by the author is normative legal research, namely research on the application of law, and it was concluded that the Legal Considerations of the Industrial Relations Court were very ambiguous and wrong in applying the law.